Examining the Relationship Between Driving Anger and the Violation of Traffic Laws and Differences Based on Gender - Getrude C. Ah Gang Grace; Shazia Iqbal Hashmi; Nurul Hudani Md Nawi; Valerie Fung Yun Li; Sharifah Haszeqah S. Jainal Abdibin (2020)
The implementation of traffic laws may promote safety and reduce potential risks for all road users. Nevertheless, not all road users, particularly drivers comply with traffic laws when they feel negative emotions, such as anger. To understand this phenomenon, a study was conducted to examine the relationship between driving anger and the violation of traffic laws. The difference between male and female drivers in terms of driving anger and the violation of traffic laws was also measured. A total of 222 drivers, 130 (58.6%) males, 91 (41%) females and one who did not mention his/her gender participated in this study, and the mean age was 34.43 years (SD=10.20). This study focused on drivers with a valid driver’s licence in the area of Kota Kinabalu, Sabah. A set of questionnaires consisting of three (3) sections was used; Section A (demographic profile comprising age, driving experience, gender, academic level, and driving experience); Section B (self-reported violation of traffic laws) and Section C (driving anger). Data were analysed using simple regression analysis and an independent t-test. The study showed that driving anger contributed to 3% of the variance in the violation of traffic laws. Moreover, the male drivers scored higher on the violation of traffic laws than the female drivers. By contrast, the female drivers scored higher on driving anger than the male drivers. The results provided an insight into the effects of anger on the violation of traffic laws and the difference between males and females in terms of driving anger and the violation of traffic laws. The outcomes can be used as guidelines for relevant authorities in creating a road safety programme that focuses on strategies for managing and controlling anger while on the road. These guidelines may reduce the negative effects of anger, such as the violation of traffic laws, on driving behaviour.